Age-Related Expression of IFN-λ1 Versus IFN-I and Beta-Defensins in the Nasopharynx of SARS-CoV-2-Infected Individuals - Gilbert, Charly; Lefeuvre, Caroline; Preisser, Laurence; Pivert, Adeline; Soleti, Raffaella; Blanchard, Simon; Delneste, Yves; Ducancelle, Alexandra; Couez, Dominique; Jeannin, Pascale (Frontiers in Immunology, 2021)
SARS-CoV-2 coronavirus infection induces heterogeneous symptoms, ranging from asymptomatic to lethal forms. Severe forms usually occur in the elderly and/or individuals with comorbidities. Children generally remain asymptomatic to primary infection, suggesting that they may have an effective local innate immune response. IFN-I and -III have non-redundant protective roles against SARS-CoV-2, although sometimes damaging the host. The expression and role of anti-viral peptides during SARS-CoV-2 infection have thus far been little studied. We aimed to identify the innate immune molecules present at the SARS-CoV-2 entry point. We analyzed the mRNA levels of type I (IFN-α and -β) and type III (IFN-λ1-3) interferons and selected antiviral peptides (i.e., β-defensins 1-3, α-defensins [HNP1-3, HD5] pentraxin-3, surfactant protein D, the cathelicidin LL-37 and interleukin-26) in nasopharyngeal swabs from 226 individuals of various ages, either infected with SARS-CoV-2 (symptomatic or asymptomatic) or negative for the virus. We observed that infection induced selective upregulation of IFN-λ1 expression in pediatric subjects (≤15 years), whereas IFN-α, IFN-β, IFN-λ2/λ3, and β-defensin 1-3 expression was unaffected. Conversely, infection triggered upregulation of IFN-α, IFN-β, IFN-λ2/λ3, and β-defensin 1-3 mRNA expression in adults (15-65 years) and the elderly (≥ 65 years), but without modulation of IFN-λ1. The expression of these innate molecules was not associated with gender or symptoms. Expression of the interferon-stimulated genes IFITM1 and IFITM3 was upregulated in SARS-CoV-2-positive subjects and reached similar levels in the three age groups. Finally, age-related differences in nasopharyngeal innate immunity were also observed in SARS-CoV-2-negative subjects. This study shows that the expression patterns of IFN-I/-III and certain anti-viral molecules in the nasopharyngeal mucosa of SARS-CoV-2-infected subjects differ with age and suggests that susceptibility to SARS-CoV-2 may be related to intrinsic differences in the nature of mucosal anti-viral innate immunity.